2016
DOI: 10.1111/ppc.12201
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Psychiatric Patients’ Perspectives on Their Care: A Narrative View

Abstract: The findings of the present study should direct the forensic psychiatric personnel's attention to the notion that forensic psychiatric patients' experiences of their treatment can improve the quality of patient-centered care and reduce bureaucracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…This can be understood as a part of the dual-role dilemma between these two roles or sets of tasks, promoting public safety on the one hand and the wellbeing of individual patients on the other hand (Robertson & Walter, 2008;Ward, 2013). Askola et al (2018) argued that patients in forensic psychiatry often begin their time in psychiatric treatment feeling a sense of alienation. Sometimes patients start fighting against the forensic psychiatric institution, while at the same time being very vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…This can be understood as a part of the dual-role dilemma between these two roles or sets of tasks, promoting public safety on the one hand and the wellbeing of individual patients on the other hand (Robertson & Walter, 2008;Ward, 2013). Askola et al (2018) argued that patients in forensic psychiatry often begin their time in psychiatric treatment feeling a sense of alienation. Sometimes patients start fighting against the forensic psychiatric institution, while at the same time being very vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Even during the twentyfirst century, research has shown that forensic psychiatric care is characterised by correction and discipline, with a caring care being overshadowed by a non-caring care. Several studies have shown that the care provided in forensic psychiatric settings can be characterised as behavioural modification and discipline (e.g., Askola et al, 2016;Barnao, Ward, & Casey, 2015;Gildberg, Bradley, Fristed, & Hounsgaard, 2012;Gildberg, Elverdam, & Hounsgaard, 2010;Holmes, 2002Holmes, , 2005H€ orberg & Dahlberg, 2015;H€ orberg et al, 2012;Jacob, 2012Jacob, , 2014Jacob & Foth, 2013). Care based on behavioural modification risks overshadowing both the patient as a person and their lifeworld.…”
Section: Forensic Psychiatric Care and Caringmentioning
confidence: 99%
“…Patients live with restrictions and confinement in an unhome‐like atmosphere where they ‘strive to convert the unfamiliar to the familiar and the impersonal to the personal’ (Olausson et al , p. 521). They may feel that they are subjected to humiliating attitudes in a prison‐like culture (Hörberg et al ) and that their opinions and rights are ignored by staff (Askola et al ; Olsson et al ). They might feel burdened by normative expectations of what recovery should look like and pressured to act adherent (Livingston ).…”
Section: Introductionmentioning
confidence: 99%